Gruppenaufnahme - Marc Darchinger
stellvertretender SPD-Vorsitzender Johannes Rau; Mitglied SPD-Parteivorstand Hans Eichel; Vorsitzender SPD-Landesverband Hessen Hans Eichel; SPD-Vorsitzender Oskar Lafontaine; Mitglieder SPD-Parteivorstand Reinhard Höppner, Ulrich Maurer und KurtBeck; Vorsitzender SPD-Landesverband Rheinland-Pfalz Kurt Beck;